Prevalence of post-traumatic stress disorder risk post-COVID-19 in 12 countries in Latin America: a cross-sectional survey - Mejia, Christian R.; Serna-Alarcón, Víctor; Vilela-Estrada, Martín A.; Armada, Jose; Ubillus, Milward; Beraún-Barrantes, Jose; Álvarez-Risco, Aldo; Del-Aguila-Arcentales, Shyla; Davies, Neal M.; Yáñez, Jaime A. (Frontiers in Public Health, 2024)
Latin America was the region most affected by COVID-19 in the second quarter of 2020, and consequently, the impact on mental health requires must be evaluationed. The aim of this study was is to assess the risk of post-traumatic stress disorder (PTSD) caused by bereavement due to COVID-19 in 12 countries in Latin America. The current study is was an analytical cross-sectional study. Validated tests were applied for PTSD, depression, anxiety, and stress (DASS-21), questions about the respondent's condition or their environment, and demographic questions, as well as the length of the suffering mourning period of suffering. The outcomes demonstrate that the PTSD risk increased for women (p <0.001), when a friend or acquaintance had COVID-19 (p = 0.002), when a close relative died from COVID-19 (p = 0.010), having severe depression (p <0.001), severe anxiety (p <0.001), severe stress (p <0.001), residing in Chile (p <0.001), Paraguay (p <0.001), Bolivia (p <0.001), Costa Rica (p <0.001) or El Salvador (p = 0.005). O, on the other hand, there was less risk of PTSD at an older age (p <0.001) or if respondents had a sentimental partner (p = 0.025). In the case of severe PTSD, there was a greater gender risk for women (p <0.001), a close relative dying from COVID-19 (p = 0.017), having severe depression (p <0.001), severe anxiety (p <0.001), severe stress (p <0.001), residing in Chile (p <0.001), Paraguay (p <0.001), Bolivia (p <0.001) and Costa Rica (p = 0.002). It was also observed that , on the other hand, there was less risk of severe PTSD at an older age demographic (p <0.001). It is can be concluded that the percentages of PTSD are high in its clinical severe presentation as severe, especially among Latin American women.